Pelatihan Penerapan Teknologi Pirolisis Asap Cair Dalam Proses Penyalaian Ikan - Hatika, Rindi Genesa; Fimawahib, Luth; Aini, Yulfita (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2024)
This community service program aims to provide technology application to traditional smoked fish entrepreneurs through training in the application of liquid smoke pyrolysis. The smoked fish business is one of the promising businesses for residents of Rokan Hulu Regency, because raw materials are abundant, easy to obtain, and relatively cheap prices and there is a high demand for smoked fish both from within and outside the Rokan Hulu Regency area. Fish smoking is intended to give aroma and preserve fish, considering that fish is an animal product that is easily subject to quality deterioration. Smoked fish found in Rokan Hulu Regency still uses hot smoking. The traditional fish smoking process has weaknesses, including food safety issues. this is because the concentration of smoke, optimal smoking time, and smoking temperature in traditional smoking are inconsistent and difficult to control. Through this training, smoking technology using liquid smoke is used to minimize food safety impacts. The results of the training show that the application of liquid smoke in the smoking process has been successful and can be used sustainably.